2014
DOI: 10.1002/cssc.201402502
|View full text |Cite
|
Sign up to set email alerts
|

Enabling LiTFSI‐based Electrolytes for Safer Lithium‐Ion Batteries by Using Linear Fluorinated Carbonates as (Co)Solvent

Abstract: In this Full Paper we show that the use of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) as conducting salt in commercial lithium-ion batteries is made possible by introducing fluorinated linear carbonates as electrolyte (co)solvents. Electrolyte compositions based on LiTFSI and fluorinated carbonates were characterized regarding their ionic conductivity and electrochemical stability towards oxidation and with respect to their ability to form a protective film of aluminum fluoride on the aluminum surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
3
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 42 publications
3
66
3
1
Order By: Relevance
“…[33,[46][47][48][49] Thisi nability may be explained by two differentr easons. One mayb et hat LiTFSI is too stable to provide fluoride anions fort he formation of the protectivea luminum (oxy-)fluorides urface layer.…”
Section: Imide-based Lithium Saltsmentioning
confidence: 97%
“…[33,[46][47][48][49] Thisi nability may be explained by two differentr easons. One mayb et hat LiTFSI is too stable to provide fluoride anions fort he formation of the protectivea luminum (oxy-)fluorides urface layer.…”
Section: Imide-based Lithium Saltsmentioning
confidence: 97%
“…The cyclic voltammetry test of LiTFSI in cyclic fluorinated carbonate F 2 EC (Fig. 8c) shows a continuous increase of the anodic current flowing comparable to F 1 EC, although the current density and the pitting corrosion is, indeed, reduced relatively to F 1 EC [10]. Indeed, only 10 cycles permit a large corrosion of aluminum, whereas 100 cycles are necessary with F 2 EC to observe pitting corrosion.…”
Section: Anodic Aluminum Dissolutionmentioning
confidence: 90%
“…Very recently, we reported that the utilization of a solvent mixture of mono-fluorinated ethylene carbonate and mono-fluorinated diethyl carbonate (1:1 by weight), containing 1 M LiTFSI, provides a solution to overcome the detrimental anodic aluminum current collector dissolution by forming a protective aluminum fluoride film on the aluminum surface [10]. Moreover, the investigation of this electrolyte composition in lithium-ion cells, comprising commercially available graphite as negative electrode and Li [Ni 1/3 Mn 1/3 Co 1/3 ]O 2 as positive material, revealed very stable cycling performance and good rate capability [10]. Nevertheless, so far only few studies were reported on the correlation between the fluorination and the physico-chemical and electrochemical properties of the fluorinated solvents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, electron conduction between the active material particles as well as between the LTO particles and the aluminum current collector certainly represent a major contribution to these interfacial phenomena. 57 The latter is frequently affected by the presence of a native oxide layer on the aluminum current collector surface, 58 potentially resulting in a reduced adhesion of the electrode coating. Basically, R int is very similar for all the three electrodes after ten cycles (Figures 8d to 8f), though slightly higher for PVdF-based ones (Figure 8d).…”
Section: 21mentioning
confidence: 99%